Pekerja VS Dunia Kerja Berbasis 4.0 - Ratna Juwita; Kardinal Kardinal (LPPM Universitas Multi Data Palembang, 2021)
The research was conducted to see the involvement of workers in the world of work based on 4.0 which prioritizes technology expertise in mobilizing company production activities. Another thing that is discussed in this study is the ability of workers in terms of education which supports the implementation of the use of technology in the world of work. The amount of wages will be given by the company in accordance with the work standards set by the company and the role of workers during the production process.